INTRAOPERATIVE IMAGE NAVIGATION: EXPERIMENTAL STUDY OF THE FEASIBILITY AND SURGEON PREFERENCE BETWEEN A STERILE ENCASED NINTENDO WIITM REMOTE AND STANDARD WIRELESS COMPUTER MOUSE. Issue 3 (7th February 2017) - Appleby, Ryan; zur Linden, Alex; Sears, William
Abstract : Diagnostic imaging plays an important role in the operating room, providing surgeons with a reference and surgical plan. Surgeon autonomy in the operating room has been suggested to decrease errors that stem from communication mistakes. A standard computer mouse was compared to a wireless remote‐control style controller for computer game consoles (Wiimote) for the navigation of diagnostic imaging studies by sterile personnel in this prospective survey study. Participants were recruited from a cohort of residents and faculty that use the surgical suites at our institution. Outcome assessments were based on survey data completed by study participants following each use of either the mouse or Wiimote, and compared using an analysis of variance. The mouse was significantly preferred by the study participants in the categories of handling, accuracy and efficiency, and overall satisfaction ( P <0.05). The mouse was preferred to both the Wiimote and to no device, when participants were asked to rank options for image navigation. This indicates the need for the implementation of intraoperative image navigation devices, to increase surgeon autonomy in the operating room.